Genomic characterization and antibiotic susceptibility of biofilm-forming Borrelia afzelii and Borrelia garinii from patients with erythema migrans - Fabrizio, Giorgia; Cavallo, Ilaria; Sivori, Francesca; Truglio, Mauro; Kovacs, Daniela; Francalancia, Massimo; D’Agosto, Giovanna; Trento, Elisabetta; Prignano, Grazia; Mastrofrancesco, Arianna; Ruzič-Sabljič, Eva; Pimpinelli, Fulvia; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundBorrelia afzelii and Borrelia garinii are the leading causes of Lyme borreliosis (LB) in Europe. Persistent LB forms may involve biofilms, potentially contributing to antibiotic tolerance.MethodsWhole genome sequencing (WGS) was conducted on 7 B. afzelii and 5 B. garinii isolates from erythema migrans skin biopsies. Biofilms were analyzed for extracellular DNA (eDNA) content and biomass. A phenol red metabolic assay assessed the minimum inhibitory concentration (MIC) and minimum biofilm inhibitory concentration (MBIC) of amoxicillin, azithromycin, ceftriaxone, and doxycycline.ResultsPhylogenetic analysis revealed B. afzelii and B. garinii formed distinct clades, while B. burgdorferi B31 clustered separately. Core genome analysis showed 38.9% of genes were shared between B. afzelii and B. garinii, decreasing to 26.1% with B. burgdorferi. The cloud genome expanded from 34.4% to 53.4% with the addition of B. burgdorferi. No antimicrobial resistance genes were detected. Surface adhesion gene profiles exhibited significant variation across species, suggesting potential functional differences in host adaptation. B. afzelii and B. garinii species exhibited biofilms, with biomass correlating significantly with eDNA production. MIC values were 0.25 μg/mL (amoxicillin, ceftriaxone), 0.125 μg/mL (azithromycin), and 0.5 μg/mL (doxycycline), with no significant interspecies differences. However, MBIC values were considerably higher: 2 μg/mL (amoxicillin, azithromycin), 16 μg/mL (ceftriaxone), and 32 μg/mL (doxycycline).ConclusionsBiofilms in B. afzelii and B. garinii significantly reduce antibiotic efficacy, particularly ceftriaxone and doxycycline. These in vitro findings highlight the need for targeted therapeutic strategies and suggest biofilms may impact treatment outcomes in LB.